Abandono familiar y su incidencia en el estado de ánimo de los adultos mayores asilados en el Hogar Geriátrico Esteban Quirola de la ciudad de Machala, año 2014. - Armijos Romero, Ariana Lizbeth (2014)
In the present field research in El Oro province, singing Machala, he was studied and analyzed how index family abandonment in the mood of the elderly refugees in the Geriatric Home Esteban Quirola, in turn have looked carefully at the causes that promote the abandonment, major mood disorders and psychological coping process experienced by the elderly abandoned in geriatric resistance